Oral steroids for the resolution of otitis media with effusion (OME) in children (OSTRICH): study protocol for a randomised controlled trial. Issue 1 (December 2016) - Waldron, Cherry-Ann; Thomas-Jones, Emma; Cannings-John, Rebecca; Hood, Kerenza; Powell, Colin; Roberts, Amanda; Tomkinson, Alun; Fitzsimmons, Deborah; Gal, Micaela; Harris, Debbie; Shepherd, Victoria; Butler, Christopher; et al.
Abstract Background Otitis media with effusion (OME) is an accumulation of fluid in the middle ear affecting about 80 % of children by the age of 4 years. While OME usually resolves spontaneously, it can affect speech, behaviour and development. Children with persistent hearing loss associated with OME are usually offered hearing aids or insertion of ventilation tubes through the tympanic membrane. Oral steroids may be a safe and effective treatment for OME, which could be delivered in primary care. Treatment with oral steroids has the potential to benefit large numbers of children and reduce the burden of care on them and on health services. However, previous trials have either been too small with too short a follow-up period, or of too poor quality to give a definite answer. The aim of the Oral Steroids for the Resolution of Otitis Media with Effusion in Children (OSTRICH) trial is to determine if a short course of oral steroids improves the hearing of children with OME in the short and longer term. Methods/design A total of 380 participants (children of 2 to 8 years of age) are recruited from Hospital Ear, Nose and Throat departments in Wales and England. A trained clinician seeks informed consent from parents of children with symptoms for at least 3 months that are attributable to OME and with confirmed bilateral hearing loss at study entry. Participants are randomised to a course of oral steroid or a matched placebo for 1 week. Outcomes include audiometry, tympanometry and otoscopy assessments; symptoms; adverse effects; functional health status; quality of life; resource use; and cost effectiveness. Participants are followed up at 5 weeks, and at 6 and 12 months after the day of randomisation. The primary outcome is audiometry-confirmed satisfactory hearing at 5 weeks. Discussion An important evidence gap exists regarding the clinical and cost effectiveness of short courses of oral steroid treatment for OME. Identifying an effective, safe, nonsurgical intervention for OME in children for use in primary care would be of great benefit to children, their families and the NHS. Trial registration ISRCTN:ISRCTN49798431 (Registered 7 December 2012)